Dinamika Dakwah di Komunitas Tilawah Tigapuluh (KTT) - Athqianita, Sheyrill; Shodiqin, Asep; Mujib, Abdul (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The purpose of this study was to find out how the dynamics of the summit's da'wah from the beginning of its formation, internal strengthening, the development of da'wah and the role of the summit in the community of Sukabumi Regency. The method used in this research is a qualitative method with a descriptive approach. The results of this study the authors found that the initial formation of the Summit was carried out with a tabligh approach through lectures in each mosque. Internal strengthening with coaching and guidance activities to regional and village coordinators. As well as the development of the summit's da'wah with the renewal of activities from year to year. The Summit acts as a forum for obtaining religious knowledge, especially in fostering reading the Al-Quran, and encouraging the public to be diligent in worshiping and giving alms.